2022
DOI: 10.3389/fmolb.2022.800888
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Crucial Hub Genes and Differential T Cell Infiltration in Idiopathic Pulmonary Arterial Hypertension Using Bioinformatics Strategies

Abstract: Background: Idiopathic pulmonary arterial hypertension (IPAH) is a life-threatening disease. Growing evidence indicated that IPAH is a chronic immune disease. This study explored the molecular mechanisms and T cell infiltration of IPAH using integrated bioinformatics methods.Methods: Gene expression profiles of dataset GSE113439 were downloaded from the Gene Expression Omnibus and analyzed using R. Protein-protein interaction (PPI) network and gene set enrichment analysis (GSEA) were established by NetworkAnal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In our study, CR1 was downregulated in PAH and positively correlated with monocytes and neutrophils, but negatively correlated with memory resting CD4 + T cells, which provided some evidence for future investigation of the mechanism of CR1-associated immune cell infiltration in PAH. TXNRD1, a member of the thioredoxin (Trx) system that catalyzes Trx1 reduction, plays a vital role in redox homeostasis [ 32 ]. In our study, it was shown that TXNRD1 mRNA was significantly decreased in human PAH lung samples by bioinformatics, which is consistent with previous reports [ 6 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, CR1 was downregulated in PAH and positively correlated with monocytes and neutrophils, but negatively correlated with memory resting CD4 + T cells, which provided some evidence for future investigation of the mechanism of CR1-associated immune cell infiltration in PAH. TXNRD1, a member of the thioredoxin (Trx) system that catalyzes Trx1 reduction, plays a vital role in redox homeostasis [ 32 ]. In our study, it was shown that TXNRD1 mRNA was significantly decreased in human PAH lung samples by bioinformatics, which is consistent with previous reports [ 6 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As high-throughput technologies have been increasingly applied in PAH, largescale data can be obtained in publicly available databases. Moreover, many studies have been performed to identify molecular biomarkers and explore the underlying mechanisms of PAH based on public data [5,[14][15][16]. Despite the recently made great efforts, Group I PAH remains largely unexplored concerning its molecular mechanism and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Nies et al found that the Insulin-like growth factor (IGF) axis could serve as a diagnostic biomarker for severe pulmonary hypertension [4]. Similarly, Yang et al uncovered mitogen-activated protein kinase 6 (MAPK6) to be an important gene for discriminating IPAH from healthy controls [5]. A few biological processes have been 2 of 24 reported to participate in developing Group I PAH; however, the search of biomarkers associated with this disease needs further exploitation.…”
Section: Introductionmentioning
confidence: 99%